Study of adverse drug reactions in a tertiary care hospital - Godbharle, Santosh B.; Padwal, Sudhir L. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The objectives of the study were to evaluate incidence and preventability of adverse drug events (ADEs) and potential ADEs and to analyse preventable events to develop prevention strategies. Methods: The study was retrospective observational study conducted at a rural tertiary care hospital at Maharashtra, for 12 months. Patients of both gender and all age group were included in the study. These entire adverse drug reactions were reported either by the PVPI assistance and/or hospital staff and their severity and causality assessments was performed as per Naranjo’s and Hartwig’s assessment criteria respectively. Data was analyzed by using Microsoft Excel. Results: There were total 256 ADR (adverse drug reactions) were reported in 12 months from January 2018 to December 2018 in various departments of the study center. Most of the adverse drug reactions were reported among age group of 21–40 years patients. Rash and itching (69) were most commonly reported ADR’s. ART (31.25%), antibiotics (28.90%) were reported to induce maximum number of ADRs. Most of the adverse drug reactions were possible (194, 75.78%) and mild (208, 81.25%) in nature. Conclusions: The antibiotics, ART drugs were most common drugs to reported ADRs. The commonly reported reactions were rash and itching.